Novel therapies for high-grade gliomas: A vision for future - Vivek Tandon; Subhashree Mahapatra; Ashok Kumar Mahapatra (Indian Journal of Neurosurgery)
The treatment for high-grade glioma remains an enigma. The standard treatment using surgery, radiation therapy and chemotherapy for such highly malignant lesions has only yielded modest results, in terms of survival and improving the quality of life of patients. Less than 10% of such patients survive beyond two years. All conventional therapies have failed to increase the survival beyond this extent. There has been a growing interest in the molecular approaches for the treatment of high-grade gliomas which include gene therapy, oncolytic virotherapy, and immunotherapy. These new therapies are in preclinical and investigational stages. They may not substitute the conventional therapies; they may not be the ultimate elixir for this deadly disease. However, in the coming years, they are likely to have synergistic and complimentary roles alongside conventional therapies. Through this paper, we have attempted to highlight the rationale behind gene therapy which can be used for cytotoxic approaches, immunomodulation strategy, and targeted toxin delivery in the tumor cell. We have reviewed current available literature and through this paper focus on reporting such therapeutic options, their potential usage, benefits and limitations.